2022
DOI: 10.1111/josh.13154
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Teacher‐Student Relationships and the Whole School, Whole Community, Whole Child Model to Mitigate Adverse Childhood Experiences

Abstract: BACKGROUND Adverse childhood experiences (ACEs) are associated with poorer health and educational outcomes. With over 20% of children experiencing multiple ACEs, interventions must target protective factors to improve outcomes among these students. Teacher‐student relationships (TSRs) integrated with the Whole School, Whole Community, Whole Child (WSCC) are one promising approach to building resilience to overcome ACEs. METHODS A narrative literature review was conducted on ACEs, resilience, TSRs, and the WSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Thus, resilience in teachers has a double aspect [ 33 ]. On the one hand, as resilient professionals, the promotion of resilience in students, influencing through the teacher’s educational practices, both in prevention (working with students to strengthen individual qualities of resilience, providing support and affection and promoting networking by involving families) as well as in intervention, when the teacher works with students who are facing an adverse situation of any kind, offering them guidelines and coping strategies and showing the importance of the environment, becoming a tutor or guide for them [ 34 , 35 , 36 ]. This strengthening of resilience reduces the likelihood of the emergence of problems associated with physical and mental health, as well as school dropout [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, resilience in teachers has a double aspect [ 33 ]. On the one hand, as resilient professionals, the promotion of resilience in students, influencing through the teacher’s educational practices, both in prevention (working with students to strengthen individual qualities of resilience, providing support and affection and promoting networking by involving families) as well as in intervention, when the teacher works with students who are facing an adverse situation of any kind, offering them guidelines and coping strategies and showing the importance of the environment, becoming a tutor or guide for them [ 34 , 35 , 36 ]. This strengthening of resilience reduces the likelihood of the emergence of problems associated with physical and mental health, as well as school dropout [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research problem addressed in this study was the negative impact of trauma on student learning outcomes, particularly during the COVID-19 pandemic. Several articles emphasized the need for trauma informed practices and connections in the classroom with the increase of trauma among students, particularly since the COVID-19 pandemic [ 6 , 7 , 20 , 21 ]. A study exploring needs of students with past trauma in the classroom, acknowledges that this is becoming the daily undertaking of teachers and identifies required teacher efficacy in the areas of social emotional learning to support these at-risk students [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that building relationships with students requires a relational perspective of interpersonal communication between teacher and student, rather than self-reflection by teachers, and that this perspective can be the focus of any teacher [ 23 ]. Yet, research shows that teachers who prioritize building relationships with their students and teaching them social emotional skills find the work challenging without the availability of trauma-informed trainings [ 20 ]. While there is some research addressing the need for bonding activities in the classroom that help build teacher student relationships during COVID-19 [ 20 , 22 , 23 ], they do not specifically address how to do these relationship building activities in online classrooms, such as the use of community circles and mindfulness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations